A Comparison of Corporate Strategic Planning Between UK and Indian Companies - DUBEY, KIRTI; JAIN, VIPIN; SHIRUR, SRINIVAS (The journal of contemporary issues in business and government, 2021)
In current years, corporate companies are paying extra attention towards developing strategic plans for their organization to develop its performance and quality of work. Firms should try to implement planning and not only any simple planning, the planning should be strategic and effective if they have to survive in today's competitive business world. The objective of the presented paper is to compare the characteristics and nature of strategic planning implemented in the companies of India and the United Kingdom. To do so, a questionnaire was sent to 500 companies from the UK and India. Based on the data collected from the companies, a comparison was done and it was found out that there are numerous differences between the implementation of strategic planning in both countries. This research provides some important facts and insights to the Eastern and Western companies, strategic planning implementation to the business.